Carbon based Y-type molecules for application in nonlinear optics. Issue 5 (6th January 2020) - Yang, Cui-Cui; He, Yuan-Yuan; Zheng, Xue-Lian; Chen, Jiu; Yang, Ling; Li, Wei-Qi; Tian, Wei Quan
Abstract : Introduction of polar azulenes and further functionalization significantly enhance the NLO properties of carbon based materials. Abstract : Inducing new nonlinear optical (NLO) properties while maintaining the thermal stability of carbon based nanomaterials broadens the application of carbon nanomaterials in opto-electronics. In the present work, polar azulene defects are introduced in Y-type carbon based molecules to induce polarity thus enhancing the second order NLO properties (for example, the static first hyperpolarizability of Y-type carbon based molecules with azulene defects reaches 4.18 × 10 −30 esu per heavy atom while that of p -nitroaniline is 2.97 × 10 −30 esu per heavy atom). The addition of an electron acceptor at the heptagon end modifies the π electron distribution of Y-type carbon based molecules and significantly enhances the static first hyperpolarizability from 1.73 × 10 −30 esu per heavy atom to 8.87 × 10 −30 esu per heavy atom, much larger than that of similarly synthesized NLO compounds. The cause of such enhancement by introduction of electron acceptors has been scrutinized.